Enhancing Humidity Performance: Effect of Electrode Material on Electrochemical Reduced Graphene Oxide (ERGO) Humidity Sensor - Khairudin, Norhazlin; Ilias, Mohammad Haziq; Abdul Rani, Rozina; Ahmad, Muhammad Zamharir; Manut, Azrif; Burham, Norhafizah; Majid Nour,; Zoolfakar, Ahmad Sabirin (International Journal of Integrated Engineering, 2022)
Reduced graphene oxide (rGO) possesses remnant oxygen functional groups, hydrophilic characteristics, and a large surface area, making it a one-of-a-kind material with unique qualities that are attributed to the reduction of graphene oxide (GO) process. There are numerous ways that can be utilized in the reduction process; however, it has not yet been completely examined which method is the most efficient in terms of reducing the oxygen-containing functional group from the GO. This is owing to the fact that a successful reduction technique has the potential to broaden the scope of rGO's applicability across a wide range of industrial sectors. Herein, in this paper, we investigated the effect of humidity performance on different metal materials such as Pt, Au, Ag, and Cu with fixed fingers spacing of 5um on the reduced graphene oxide (rGO) by electrochemical deposition (ECD) from GO aqueous dispersion. A combination of experimental measurements using humidity chamber, Raman spectroscopy, Electrochemical Impedance Spectroscopy, and Scanning Electron Microscopy has revealed the performance of rGO as the humidity sensor. The finding shows, rGO/Pt displayed good humidity performance, as demonstrated by its higher sensitivity and greater response towards humidity, which are both enhanced by its stronger ionic conductivity.